Effect of anticipation during unknown or unexpected exercise duration on rating of perceived exertion, affect, and physiological function - Baden, D. A.; McLean, T. L.; Tucker, R.; Noakes, T. D.; St. Clair Gibson, A. (British Journal of Sports Medicine, 2005)
Objectives: To determine the effect of unknown exercise duration and an unexpected increase in exercise duration on rating of perceived exertion (RPE), affect, and running economy during treadmill running.